2019
DOI: 10.1017/s1751731119001423
|View full text |Cite
|
Sign up to set email alerts
|

Correlated responses on growth traits after two-stage selection for ovulation rate and litter size in rabbits

Abstract: Rabbit commercial maternal lines are usually selected for litter size (LS) and paternal lines for growth rate (GR). Line OR_LS was selected by ovulation rate (OR) and LS to improve LS more efficiently. In this study, growth traits of line OR_LS were evaluated by estimating the correlated response on weaning weight (WW), slaughter weight (SW) and GR during fattening period as well as their variability (DWW, DSW and DGR, respectively). Data were analyzed using Bayesian inference methods. Heritability estimates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 14 publications
13
11
0
Order By: Relevance
“…This has implications for animal welfare, since animals that cope better with their environment have better welfare than more sensitive animals [7]. After correcting for litter size, both lines had similar individual weight at birth, and survival at birth and survival at 4 days of age were [15].…”
Section: Correlated Response To Selection In Litter Survival and Prewmentioning
confidence: 99%
“…This has implications for animal welfare, since animals that cope better with their environment have better welfare than more sensitive animals [7]. After correcting for litter size, both lines had similar individual weight at birth, and survival at birth and survival at 4 days of age were [15].…”
Section: Correlated Response To Selection In Litter Survival and Prewmentioning
confidence: 99%
“…Regarding the reproductive traits, they present low-to-moderate genetic correlations with growth traits in pigs (Holm et al, 2004;Skovsted et al, 2005; Rothschild and Ruvinsky, 2011), minks (Karimi et al, 2018), mice (Malik, 1984), rats (Eisen, 1976), rabbits (Garreau et al, 2004;Peiró et al, 2019) and all polytocous species. In rabbits, estimations of genetic correlations amongst reproductive traits and body weight traits within lines were low (Garcıá and Baselga, 2002;Peiró et al, 2019) or inconsistent (Camacho and Baselga, 1990), since studies suggested positive and negative correlations between them (Camacho and Baselga, 1990;Bünger et al, 2005). For instance, genetic correlations between litter size and weaning weight, slaughter weight, and growth rate were -0.11, 0.03 and 0.11, respectively (Peiró et al, 2019).…”
Section: Relationship Between Growth Meat and Litter Size Traitsmentioning
confidence: 99%
“…In rabbits, estimations of genetic correlations amongst reproductive traits and body weight traits within lines were low (Garcıá and Baselga, 2002;Peiró et al, 2019) or inconsistent (Camacho and Baselga, 1990), since studies suggested positive and negative correlations between them (Camacho and Baselga, 1990;Bünger et al, 2005). For instance, genetic correlations between litter size and weaning weight, slaughter weight, and growth rate were -0.11, 0.03 and 0.11, respectively (Peiró et al, 2019). Garcıá & Baselga (2002) found very low genetic correlation (0.06) between ADG and litter size.…”
Section: Relationship Between Growth Meat and Litter Size Traitsmentioning
confidence: 99%
See 2 more Smart Citations